An Agreement Analysis on the Perception of Property Stakeholders for the Acceptability of Smart Buildings in the Nigerian Built Environment - Alohan E.O.; Oyetunji A.K.; Amaechi C.V.; Dike E.C.; Chima P. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The introduction of intelligent devices in buildings has brought about tremendous changes into the construction industry. The use of automation is also gradually gaining interest from the stakeholders involved in the built environment. This paper presents the perception of property stakeholders (property valuers/real estate developers and service users) regarding the acceptability of smart buildings as a future built environment in Nigeria, using Benin City a case study. A total of 159 structured questionnaires were administered with 108 retrieved and valid for analysis. The information sourced from the respondents includes smart building awareness, the support for, drivers to, and limitations of its implementation, the willingness to develop smart buildings, and the willingness to pay proportionate rent to occupy smart properties. The findings showed that the poll of respondents for the property valuers and the real estate developers, as well as the service users, claimed to be aware of the concept, and they also support its development in the country. The drivers and limitations were ranked based on their perceived level of significance. This study recommends the promotion of awareness to accelerate its acceptance and implementation. This will help propagate the process of creating a smart city in developing nations such as Nigeria and prepare property valuers professionally for its management. 2023 by the authors.